2014
DOI: 10.1089/ten.tec.2013.0270
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized Kidney Matrix for Perfused Bone Engineering

Abstract: The vascularization of tissue-engineered constructs is yet an unsolved problem. Here, recent work on the decellularization of whole organs has opened new perspectives on tissue engineering. However, existing decellularization protocols last several days and derived biomatrices have only been reseeded with cells from the same tissue origin or stem cells differentiating into these types of tissue. Within the present work, we demonstrate a novel standardized, time-efficient, and reproducible protocol for the dece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 19 publications
1
28
0
Order By: Relevance
“…Since the first report describing perfusion of detergents through the coronary arteries of rodent hearts by Ott and Taylor in 2008 (11), several approaches to remove cells from the heart (34), liver (13, 23, 35) and lung (12, 36) have been described. Likewise, a variety of perfusion decellularization protocols for kidney have been tested for rodents, pigs, and humans (reviewed in 10 and described in 1416, 18, 19, 37, 38), but few studies report data specifically comparing the influence of different chemical-based decellularization procedures on resulting ECM architecture and sufficiency for supporting recellularization (14, 39). …”
Section: Discussionmentioning
confidence: 99%
“…Since the first report describing perfusion of detergents through the coronary arteries of rodent hearts by Ott and Taylor in 2008 (11), several approaches to remove cells from the heart (34), liver (13, 23, 35) and lung (12, 36) have been described. Likewise, a variety of perfusion decellularization protocols for kidney have been tested for rodents, pigs, and humans (reviewed in 10 and described in 1416, 18, 19, 37, 38), but few studies report data specifically comparing the influence of different chemical-based decellularization procedures on resulting ECM architecture and sufficiency for supporting recellularization (14, 39). …”
Section: Discussionmentioning
confidence: 99%
“…Decellularizing cadaveric organs maintains the macro and micro architectures of the organ along with the natural ECM composition, thereby providing a platform for recellularization and regeneration of the organ [1]. Perfusion decellularization has been used on lungs, livers, kidneys, and hearts from rats, mice, pigs, and humans to create acellular organ scaffolds [1019]. The process of perfusion decellularization requires flowing the decellularizing reagents through native arteries at physiological pressures in order to enter the innate blood vessel system and reach every cell [20].…”
Section: Preparation Of Decellularized Materialsmentioning
confidence: 99%
“…Burgkart et al had a unique experimental set up where they showed that a decellularized kidney could be used for bone engineering because the intact vasculature provided nutrients to the osteoblasts. In this study they perfused a whole decellularized rat kidney with primary human osteoblasts using osteogenic media and saw that the osteoblasts kept their phenotype and reconstructed the matrix [19]. These results highlight that there is still little understood about the kidney ECM niche and how it can affect differentiation.…”
Section: Ecm Effects On Cell Differentiationmentioning
confidence: 99%
“…The goal of the described decellularization protocol is to produce an acellular renal ECM that can be used as a 3D scaffolding system for regeneration of kidney structures, including nephron tubules that are repopulated in the present example with human renal cortical tubular epithelial (RCTE) cells. We previously described our rigorous evaluation of an optimal, detergent-based rat kidney decellularization protocol 7 , which is more rapid (approximately one day) than other methods previously reported (Ross et ), and exposes the organ to a considerably lower concentration (0.1%) of the denaturant sodium dodecyl sulfate (SDS) during decellularization than prior reports [12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of studies have described the use of rodent kidneys for decellularization and subsequent use as a 3D scaffold for cellular repopulation (reviewed elsewhere 1 ) [12][13][14][15][16] . In this protocol, we provide a detailed description of our previously established, optimal decellularization strategy for producing acellular kidney scaffolds from Sprague Dawley rat kidneys 7 .…”
Section: Introductionmentioning
confidence: 99%